COMPARATIVE ANALYSIS OF UPPER-SARMATIAN DIATOMACEOUS COMPLEXES FROM THE ZELENSKY AND KOPTA-KYL ANTICLINES - MELNYK, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The results of research of Taman and Kerch peninsulas upper-sarmatian diatomaceous complexes are described. Species composition of these complexes and terms of sedimentation in the paleobasin are compared.